Price Surges in Basic Necessities — Redistribution of Burdens Required - Irene Becker (Wirtschaftsdienst)
Abstract Since the beginning of 2022, prices for food and energy have been rising sharply. In the low-income sector, this leads to financial emergencies, since the standard of living here is far below the standards of society anyway. On the other hand, the consequences of inflation can certainly be absorbed in the upper income brackets. Against this background, government measures should be concentrated on lower income brackets. Appropriate measures would be the payment of inflation compensation for those receiving basic security, a reform of the updating of basic security benefits and an income-related transfer payment for households without basic security. A solidarity surcharge on the income tax is proposed for financing.